Hamlet (RSC, 2016) and representations of diasporic blackness. Issue 1 (July 2019) - Iyengar, Sujata; Feracho, Lesley
In 2016 Paapa Essiedu, a British actor of Ghanaian ancestry, starred as Hamlet in Simon Godwin's lauded Royal Shakespeare Company (RSC) production, set in a post-colonial African state whose non-specificity nonetheless irritated some reviewers. We contend, however, that the production mixed multiple referents of blackness (Eastern African, West African, Caribbean, South African, 1970s African American) in order deliberately to create an imaginary post-colonial domain where these different kinds of diasporic blackness engaged with each other through the figure of Hamlet and his art. We therefore examine how the concept of race changes with the transatlantic or transnational movement among spaces in this production.